Ensino do tato de propriedaes sensoriais no contexto do brincar simbólico para crianças com austimo - Urzêda, Gabriela Alexandre Ribeiro (2024)
Children diagnosed with Autism Spectrum Disorder (ASD) often engage in repetitive and solitary activities and exhibit a significant deficit in the repertoire of symbolic play. Symbolic play is crucial for the development of social, cognitive, language, and emotion expression skills. The present study aimed to evaluate an intervention procedure using interactions with real objects to teach or enhance the attribution of pretend properties to mock (non-real) and arbitrary objects. Six children diagnosed with ASD, aged 4 to 7 years, participated, interacting with real objects and were asked to tact the sensory properties during the intervention. Corresponding test objects, the mock objects (e.g., a toy candy) and arbitrary objects (e.g., blue tissue paper), were used to assess whether the responses of tact sensory properties would transfer. A multiple probes design across objects was employed. The results indicated that one child emitted tacts of stimulus properties for all three test objects presented, and one child emitted tacts of stimulus properties for one of the test objects. Another participant showed an increase in tacts of sensory properties in two items compared to the baseline. One participant maintained the initial performance, and two participants had their data collection interrupted. The application of resources and efforts in an experimental study on this theme aims at the development of teaching procedures that can be useful for professionals working with intervention for children with ASD.